Herds on green meadows: the decarbonization of institutional portfolios - Lukas Benz; Andrea Jacob; Stefan Paulus; Marco Wilkens (Journal of Asset Management, 2020)
We analyze an emerging sustainable trend in asset management: the decarbonization of institutional portfolios. By using broad institutional ownership data, we show that investors exhibit herding behavior in the sense of decarbonization. They are inclined to follow their own or other investors' buys in green stocks and sales in brown stocks over adjacent quarters. Beyond that, we find that Hedge Funds as well as Investment Advisors lead the herd by executing trades in the sense of decarbonization. This is in line with expectations that sophisticated investors, who integrate environmental aspects into their investment decision process, are able to attract imitators. For the aspired achievement of market-wide decarbonization, investors leading the herd should be encouraged to further decarbonize their portfolios in order to trigger follow-up trades.
Keywords: G11; G15; G23; M14; 330; Decarbonization; Institutional investors; Herding